Nursing personnel management during COVID-19 pandemic: An exemption trend in view of health reasons - Sharma, Sruti; Dhaliwal, Navneet; Bhadada, Sanjay; Kumar, Ashok; Sangat, Sumit Kumar; Pandey, Navin (Frontiers in Public Health, 2022)
Background In the COVID-19 pandemic, the healthcare system faced unprecedented challenges with increased number of patients and limited resources. Managing nursing resource was a major challenge for hospital administration. They had to be on the frontline, but their safety was of paramount importance. Aim This study aims to analyze the measures taken for the management and effective engagement of nursing personnel for deployment in the COVID area of the hospital and the exemption trend based on their health status. Methodology A retrospective cross-sectional descriptive study was carried out to analyze the requests of nursing staff received for exemption of duty in COVID patient care areas. These requests were categorized and examined by the medical board constituted for this purpose. Microsoft Excel was used to interpret the results. Results The study evaluated the health reasons of nursing officers on the basis of which exemption was given for deployment of nursing officers in COVID areas. They were mostly medical reasons (91.1%) and few personal reasons (8.77%). The majority suffered from diseases affecting two or more than two specialties. Out of 376 applications, 223 were exempted, 81 were not exempted, 13 were given short-term exemption, and 26 were shifted to administrative assignments. Thirty-three staff members were referred to an appropriate forum.